Community booklet on certified seed for rice - Lengewa, C.; Mikhala, A.; Aura, S.; Amuda, A.; Yila, Jummai; Bomuhangi, Allan; Nchanji, Eileen (2024)
Rice is an important food for many people in Uganda and across the world. It is a cereal grain that comes in various types such as long- grain, medium-grain, and short-grain. Each type has its characteristics in terms of texture, flavor, colour, etc. Today in this booklet, let us briefly discuss the benefits of certified seeds for rice, including the opportunities in agri-business for farmers, women and youth.